Water and marsh birds of middle Vistula River during breeding season: the impact of human activities on the distribution, abundance and richness of species - Bukaciński, Dariusz; Bukacińska, Monika; Buczyński, Arkadiusz (Studia Ecologiae et Bioethicae, 2011)
The inventory of birds was conducted in the years 2005-2010 on the Vistula River section between Dęblin (388 km of the river) and Podwierzbie (435 km of the river). The study area includes a southern section of the European Ecological Natura 2000 Site in Poland PLB140004 „Middle Vistula River Valley” (IBA, PL083). In most areas the Vistula flows here within unregulated or relatively little modified riverbed, having features of natural, lowland, braided river. Sandy islands and braid bars within the main channel, steep banks, and old riparian afforestation create the unique breeding habitats of the Vistula River Valley. Especially the river channel habitats provide suitable breeding sites for many rare bird species, constituting some of them the key-breeding sites. There are, however, fragments of several kilometers, where people transformed the Vistula River in a more visible way (Table 1). These are, among others: an urban section within Dęblin boundaries (km 388-393 of the river), a fragment adjacent to Kozienice Power Plant (km 421-426), and the area, where since 2007 gravel for the industry has been mining from the river bottom (km 426-431). The aim of this inventory was the comparison of richness and abundance of breeding bird species associated directly with the river channel on fragments mentioned above. It will allow us to estimate soberly how very the intensity of human utilization of the river affects the distribution of avifauna of the Vistula, determining the richness and abundance of valuable and/or endangered species breeding in a given area.